The Arctic: The Physical Environment - Christensen, Kyle D. (2010)
The Canadian Forces Maritime Warfare Centre was tasked by the Directorate of Maritime Strategy, on behalf of the Director General Maritime Force Development, to develop an Arctic Maritime Strategic Operating Concept(SOC) that would articulate potential future roles for maritime forces in the Arctic within a Canadian Forces/Government of Canada context. This Memorandum paper contributes to the development of an Arctic Maritime SOC by assessing the physical aspects of the Arctic environment with a particular emphasis on existing data, research, and literature on the impact of climate change in the north. It is conducted as an area study to facilitate the Maritime Staff's baseline of knowledge and understanding of the Arctic environment in a potentially climate-changed world. The Memorandum also examines Canadian Arctic maritime security and defence issues over the next two and a half decades and beyond, highlights those areas considered relevant to Arctic maritime operations, and identifies some future maritime defence requirements in the Arctic. Research was based on an analysis of open source literature, electronic sources, published and unpublished reports and papers, and interviews. The broad conclusion to be drawn from the Memorandum is that regardless of the possible impact of climate change in the north, there are important operational considerations to take into account when deploying to/in the Arctic. The original document contains color images.